'I'm the centre part of a Venn diagram': belonging and identity for Taiwanese-Australian intercountry adoptees. (March 2021) - Stoddart, Jennifer; Wright, Amy Conley; Spencer, Margaret; Wichelen, Sonja van
Intercountry adoptees face many challenges in developing their identity and achieving a sense of belonging in post-assimilation Australia. This study uses a constructivist approach to analyse narrative interviews with a sample of Taiwanese intercountry adoptees in Australia ranging in age from early to middle adulthood. Social identity theory and postcolonial theory are used to frame thematic findings about the impact of micro, meso and macro influences on identity development and belonging. The article concludes with discussion of the importance of analysing the impact of colonisation and broader societal discourse in social work practice when working within the adoption sector.